UNFOLDING PERFORMANCE OF FOLDING WING FOR ACTUATOR AND EXPERIMENT - LIU DuanChen; HAN XueFeng; ZHANG Yue; ZHANG MingYue; LIU XiaoDong (Jixie qiangdu)
In order to study the parameters of a folding wing‘s spreading performance which is used on the guided missile’s actuator,the unfolding performance was researched. First,a kinetic equation based on Lagrange’ s Equation was established,which provided a theoretic base for the simulation. Then,related dates such as deployable time,impact and stress of the rudder slice were obtained by rigid-flexible coupling dynamics imitating analysis of the spreading process through MSC. ADAMS.Finally,characters of the spreading performance and weak points affected by the impact were tested by experiments. The results show that the unfolding time is 175 ms,impulse strength is 42. 9N,which is less than the strength of the material,and meets the requirements of design. The performance can be described accurately by the simulation mode. Results of both simulations and experiments can provide theoretical basis for structural design and optimizing.